Multiaxial fatigue of extruded ZK60 magnesium alloy. Issue 10 (17th June 2019) - Albinmousa, Jafar; Adinoyi, Muhammed J.; Merah, Nesar
Abstract: Multiaxial monotonic and cyclic behaviors of ZK60‐T5 magnesium extrusion are investigated. Strain‐controlled tests were performed at standard laboratory condition with fully reversed straining. Twinning‐detwinning deformation plays an important role in the cyclic axial behavior for tests that were performed under strain amplitudes higher than 0.4%. However, the hysteresis loop for the 0.4% was found symmetric and no sign of twinning‐detwinning deformation was observed. On the contrary, the cyclic shear behavior was found to be similar to conventional alloys and no significant asymmetric or twinning‐detwinning deformations were observed. The multiaxial fatigue tests suggest that multiaxiality and nonproportionality are not detrimental to fatigue life. Three multiaxial fatigue damage models were used: Smith‐Watson‐Topper, Fatemi‐Socie, and Jahed‐Varvani. While Fatemi‐Socie and Jahed‐Varvani models show comparable estimation, Smith‐Watson‐Topper overestimates shear and nonproportional lives.